2018
DOI: 10.1093/cid/ciy908
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Early Valve Surgery on Survival in Staphylococcus aureus Infective Endocarditis Using a Marginal Structural Model Approach: Results of a Large, Prospectively Evaluated Cohort

Abstract: Background The impact of valve surgery on outcomes of Staphylococcus aureus infective endocarditis (SAIE) remains controversial. We tested the hypothesis that early valve surgery (EVS) improves survival by using a novel approach that allows for inclusion of major confounders in a time-dependent way. Methods EVS was defined as valve surgery within 60 days. Univariable and multivariable Cox regression analyses were performed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Real-time and adequate antibiotic treatment is insufficient in these patients; hence, sepsis is the major cause of death in these patients. Second, several studies have found that Staphylococcus aureus infection is associated with higher mortality rates in a variety of infectious diseases [40,41,42,43]. The higher rate of Staphylococcus aureus infection in diabetic patients conveys an important message, that is, this infection is associated with higher rates of both complications and mortality in IE, and these findings have been confirmed by several studies [42,43,44,45].…”
Section: Discussionmentioning
confidence: 75%
“…Real-time and adequate antibiotic treatment is insufficient in these patients; hence, sepsis is the major cause of death in these patients. Second, several studies have found that Staphylococcus aureus infection is associated with higher mortality rates in a variety of infectious diseases [40,41,42,43]. The higher rate of Staphylococcus aureus infection in diabetic patients conveys an important message, that is, this infection is associated with higher rates of both complications and mortality in IE, and these findings have been confirmed by several studies [42,43,44,45].…”
Section: Discussionmentioning
confidence: 75%